The Implementation of a spatial model for developing a flood early warning system in the Kelep River Basin, Lombok, Indonesia: Implementasi model spasial untuk pengembangan sistem peringatan dini banjir di Daerah Aliran Sungai Kelep, Lombok, Indonesia - Sugiarta, Lalu Ade; Virgota, Arben; Farista, Baiq; Widiyanti, Astrini (Indonesian Journal of Tropical Biology, 2025)
Indonesia, including in the Kelep Watershed, Lombok Island, flood disasters frequently occur. Land use changes and climate variability make this area more vulnerable to floods. This study aims to analyze the distribution and level of flood vulnerability and the dominant factors causing flood vulnerability in the Kelep Watershed. The method used was the weighting of six parameters, namely slope, landform, soil type, rainfall, land use, and river buffer, which were then overlaid using ArcGIS 10.8 software. The results showed that the highly flood-prone areas were spread across all sub-districts in the Kelep watershed, with the highest concentration in Sekotong, Lembar and Southwest Praya sub-districts. The three villages with the highest flood-prone areas are Candi Manik, Sekotong Tengah and Taman Baru. These areas require special attention as they often experience serious impacts due to flooding. Based on the validation test, the RMSE value of 5.95% indicates acceptable accuracy. The resulting flood vulnerability classification map can be used as a flood early warning system or basis for flood risk mitigation and is proposed to be implemented through cross-sector collaboration to improve preparedness and reduce disaster impacts.